Potestas Quaerens Auctoritatem. Political Theology between Hierateuma and Strateuma - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 2018)
[only abstract in English; full article and abstract in Lithuanian] This article discusses the concept of the quality of being political and the relationship between power and authority. The theories of Carl Schmitt and Eric Voegelin were chosen as the main points of reference. Problems of the interaction of power and authority are discussed in the paper as well as the genesis of the quality of being political. The article attempts to prove that the phenomenon of power occurs in the Iron Age with the disappearance of the Eastern dominances. The prominence of a principle of supremacy of power becomes an issue when the authority, which demands hierarchy and alludes to the traditions of dominance, is sought to be eliminated.